Pengetahuan Hakikat Sains (Nature of Sains - NoS) Siswa SMP Negeri dan SMP Islam: Tinjauan Berdasarkan Gender - Jufri, A Wahab; Nirmala, Siska Ayu; Munib, Munib; Dewi, Earlyna Shintia (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to analyze the level of junior high school students' knowledge of the Nature of Science (NOS) based on school type (public and Islamic junior high schools) and gender. This study is a descriptive quantitative research involving 180 students with details of 81 students from public junior high schools and 99 students from Islamic junior high schools determined by random sampling technique. The sample consisted of 104 female students and 76 male students. The research data were collected using an instrument in the form of a questionnaire that has been tested for validity and reliability based on a Likert scale developed based on NOS aspects. The results showed that (1) there was a significant difference in the understanding of NOS between students of public and Islamic junior high schools, where students of public junior high schools had a higher level of understanding (good category) than students of Islamic junior high schools (moderate category); (2) there was no significant difference in the understanding of NOS based on gender.